If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(u + -7) + -7u = -17 Reorder the terms: 3(-7 + u) + -7u = -17 (-7 * 3 + u * 3) + -7u = -17 (-21 + 3u) + -7u = -17 Combine like terms: 3u + -7u = -4u -21 + -4u = -17 Solving -21 + -4u = -17 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -4u = -17 + 21 Combine like terms: -21 + 21 = 0 0 + -4u = -17 + 21 -4u = -17 + 21 Combine like terms: -17 + 21 = 4 -4u = 4 Divide each side by '-4'. u = -1 Simplifying u = -1
| 4w+15=38 | | C-34.5=201.9 | | x^3+10=-17 | | 6a-2b=10d+6 | | 4/5m=12 | | 2x^3+10=-44 | | 2(2x+3)=3(5-2x) | | 45r^2-120rs=-80s^2 | | x^4+5x^3-2x^2+10x=0 | | 5x^2=-2x+17 | | F(x)=x^2-4 | | y=3*-1 | | -18=-2x | | 32+x=123 | | 0=12m^2-44m-16 | | 2x-124=628 | | z+70=29 | | 3x+y=13-4x | | 8x(6-4)=2(6x+4) | | 2x^2=-54 | | (5-4y)-y=16 | | 5(m+3)+7m=3(m+10) | | 9p+3=7p+4 | | 23x-3=3x+9 | | 9.5=3f-22 | | 16t^2-32t+5=0 | | 2x^2+12xy=-18y^2 | | 96=-6x | | 8(7x-3)=39 | | -30.7/-3 | | 2x^2-12xy=-18y^2 | | -13c+c= |